IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN SMALL AND MEDIUM ENTERPRISES (SMEs) - Supriyadi, Supriyadi; Abdullah, M. Wahyuddin (Jurnal Iqtisaduna, 2019)
The purpose of this paper is to find out the concept of Islamic business ethics and its implementation in Small and Medium Enterprises (SMEs). Small and Medium Enterprises (SMEs) are individual businesses or business entities that are currently experiencing rapid development. Its development certainly must be accompanied by ethical awareness as exemplified by Rasulullah saw. which is actualized through his characteristics. Thus, the business carried out is not just to get profit only but also blessing. Therefore, Islamic business ethics in Small and Medium Enterprises (SMEs) is very important to implement.